Weak versus strong sustainability exploring the limits of two opposing paradigms - Neumayer, Eric 1970- (Edward Elgar, 2010)
1. Introduction and overview -- 2. Sustainable development : conceptual, ethical and paradigmatic issues -- 3. Resources, the environment and economic growth : is natural capital substitutable? -- 4. Preserving natural capital in a world of risk, uncertainty and ignorance -- 5. Measuring weak sustainability -- 6. Measuring strong sustainability -- 7. Conclusions
Previous ed.: 2003
Includes bibliographical references (p. 210-259) and index
Keywords: Electronic books; Environmental economics; Sustainable development